Perancangan Model Bisnis Usaha Produk Dadih Susu Sapi Kedalam Kanvas Model Bisnis dan Peta Empati - Delfitriani Delfitriani (Universitas Djuanda, 2019)
The substitution of raw material for dadih product into cow's milk is an effort to overcome the limitations of buffalo milk. This business needs to be analyzed regarding business aspects amid the intense competition of fermented milk products on the market. The purpose of this study was to analyze the business model of cow milk dadih products using the model business canvas and to map the needs of consumers of dadih products using empathy maps. The results of the business model analysis shown that dadih products have the potential to be developed to expand market reach. Customer segmentation needs to be expanded using the proportion of values that have been designed and promoted with the help of all parties, including the support of the West Sumatra government. Empathy map provides an overview of dadih product manufacturers about the needs and desires of consumers of dadih products.